Use of levosimendan in acute and advanced heart failure: short review on available real-world data - Pashkovetsky E; Gupta CA; Aronow WS (Dove Medical Press, 2019)
Eugene Pashkovetsky, Chhaya Aggarwal Gupta, Wilbert S AronowDivision of Cardiology, Department of Medicine, Westchester Medical Center and New York Medical College, Valhalla, NY 10595, USAAbstract: Published data have shown potential advantages of levosimendan in the management of acute decompensated heart failure and advanced heart failure when standard medical therapies threaten hemodynamics and organ perfusion are unable to alleviate clinical symptoms. Levosimendan distinguishes itself from other catecholaminergic inotropes by its three mechanisms of action: positive inotropy, vasodilation, and cardioprotection. In addition, its pharmacokinetics allow for a longer duration of action from the metabolite OR1896 allowing for further cardiovascular therapeutic effects for several days, even after discontinuation of the parent drug.Keywords: levosimendan, heart failure, inotropic therapy